Analisis Kualitas Produk dan Harga Terhadap Keputusan Pembelian Produk Garnier Micellar Water Studi pada Masyarakat Kota Ambon - Ance Letelay; Geradin Rehatta; Francisca Riconita Sinay (Jurnal Pendidikan Ekonomi, 2025)
The growing demand for facial care products drives consumers to seek both quality and affordability. This study aims to analyze the influence of product quality and price on purchasing decisions of Garnier Micellar Water among Ambon City residents. A quantitative associative method was applied through questionnaires distributed to 60 respondents. Regression analysis shows that both product quality and price have a positive and significant effect, individually and simultaneously, on purchase decisions. These findings suggest that consumers' perceptions of quality and price-benefit alignment play a vital role in shaping their final decisions. The determination coefficient of 27.4% reflects the contribution of these two variables to purchasing behavior. This study offers new insights that local consumer preferences are shaped by a combination of value perception and brand trust. It is recommended that producers maintain product quality, set competitive prices, and enhance brand communication through promotional strategies tailored to community needs